Lithium secondary battery

By adjusting the initial efficiency and size difference between the positive electrode and the negative electrode in the lithium secondary battery, the problem of degradation of cyclic performance caused by volume changes during the charging and discharging of silicon-based negative electrodes is solved, and high capacity, high energy density and fast charging are achieved.

CN119497915APending Publication Date: 2025-02-21LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380054816.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-27
Filing Date
2023-12-22
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

When using silicon-based negative electrodes, it is difficult to achieve both high capacity and fast charging, and the volume changes of the silicon-based negative electrodes lead to a degradation of cycling performance.

Method used

By adjusting the differences in initial efficiency, area ratio, full width and full length between the positive electrode and the negative electrode, we ensure that the silicon-based negative electrode does not undergo a rapid change in volume during discharge, thereby improving the cycling performance of the battery.

Benefits of technology

It achieves the balance of high capacity, high energy density and fast charging performance of lithium secondary batteries, extends the cycle life of the battery and improves the stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119497915A_ABST
    Figure CN119497915A_ABST
Patent Text Reader

Abstract

The present application relates to a lithium secondary battery which is characterized in that a silicon-based negative electrode is used to secure capacity characteristics and fast charging performance, while using an NCM (A)-based active material as a positive electrode, and in particular, by adjusting the difference in area, overall width, and overall length between the positive electrode and the negative electrode, the capacity characteristics and fast charging performance are ensured. The present invention makes it possible to adjust to a section accompanying a rapid change in volume in which a silicon-based negative electrode is not used during discharge, and makes it possible to improve cycle performance of a lithium secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0186045 filed in the Korean Intellectual Property Office on December 26, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present application relates to a lithium secondary battery. Background Art

[0003] As a part of the increasing demand for the use of alternative or clean energy due to the rapid increase in the use of fossil fuels, the most actively researched field is the field of power generation and storage using electrochemical reactions.

[0004] Currently, secondary batteries are a representative example of electrochemical devices utilizing such electrochemical energy, and the scope of use thereof tends to be gradually expanded.

[0005] As the technology development and demand for mobile devices increase, the demand for secondary batteries as energy sources has increased dramatically. Among such secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, as electrodes for such high-capacity lithium secondary batteries, the manufacturing method of high-density electrodes with higher energy density per unit volume is being actively studied.

[0006] Generally, a secondary battery comprises a positive electrode, a negative electrode, an electrolyte and a separator. The negative electrode comprises a negative electrode active material for inserting and extracting lithium ions from the positive electrode. As negative electrode materials, carbon-based materials such as graphite are excellent in stability and reversibility, but have limitations in capacity. Therefore, in the field of high capacity, there are more and more attempts to use Si-based materials with high theoretical capacity as negative electrode materials.

[0007] That is, lithium secondary batteries are generally made by combining a compound such as LiCoO 2 or LiMn 2 O 4 It is manufactured by using a material that is not embedded with lithium, such as a carbon-based or Si-based material, for the positive electrode and using a material that is not embedded with lithium, such as a carbon-based or Si-based material, for the negative electrode. During charging, the lithium ions embedded in the positive electrode move to the negative electrode through the electrolyte. During discharge, the lithium ions move back to the positive electrode from the negative electrode. During charging, the lithium moving from the positive electrode to the negative electrode reacts with the electrolyte to form a passivation film, namely the solid electrolyte interface (SEI), on the surface of the negative electrode. SEI inhibits the migration of electrons required for the reaction between the negative electrode and the electrolyte, prevents the decomposition of the electrolyte, and thus stabilizes the structure of the negative electrode. On the other hand, the formation of SEI is irreversible, resulting in the consumption of lithium ions. That is, the lithium consumed due to the formation of SEI no longer returns to the positive electrode during the subsequent discharge process, resulting in a decrease in battery capacity.

[0008] On the other hand, as an effort to improve the performance of lithium secondary batteries, it is necessary to develop technologies that speed up the charging speed. In order to quickly charge lithium secondary batteries, the migration rate of lithium ions should be fast during the process of lithium ion embedding into the negative electrode. Therefore, a battery is being designed that reduces the diffusion distance of lithium by forming a negative electrode active material layer with a thickness at the level of a thin film, and increases conductivity by forming a carbon coating on the surface of the negative electrode active material layer to reduce internal resistance, thereby achieving high output.

[0009] However, it is difficult to achieve high capacity with such a thin film negative electrode active material layer. In addition, it is difficult to achieve fast charging in a negative electrode with high capacity. In addition, when a silicon-based negative electrode is used, the content of Si in the negative electrode is increased in order to increase the energy density. Therefore, due to the reduced efficiency of the high Ni positive electrode as a positive electrode material, an excessive amount of sacrificial positive electrode material is applied to balance with the negative electrode. However, in this case, the gas generation of the battery cell itself is increased and the resulting stability problems are caused.

[0010] Therefore, for lithium secondary batteries that use a silicon-based negative electrode and a NCMA-based or NCM-based positive electrode with a high nickel content as a counter electrode in order to achieve capacity characteristics, high energy density and fast charging performance, in order to improve performance, it is necessary to study the interval in which the volume change is not used during charge and discharge, and the efficiency relationship and area relationship between the positive and negative electrodes.

[0011] Prior art literature

[0012] (Patent Document 1) Japanese Patent Application Publication No. 2009-080971 Summary of the invention

[0013] Technical issues

[0014] As a result of studying the above-mentioned problems, it can be confirmed that by using a silicon-based negative electrode to ensure capacity characteristics and fast charging performance and using NCM(A)-based active materials for the positive electrode, in particular, by adjusting the initial efficiency between the positive electrode and the negative electrode and adjusting the differences in area, full width and full length between the positive electrode and the negative electrode, the interval of rapid volume change associated with the silicon-based negative electrode is not used during discharge.

[0015] Therefore, the present application relates to a lithium secondary battery in which the area ratio of the positive and negative electrodes and the initial efficiency are adjusted.

[0016] Technical Solution

[0017] One exemplary embodiment of the present specification provides a lithium secondary battery, comprising: a positive electrode; a silicon-based negative electrode; a separator disposed between the positive electrode and the negative electrode; and an electrolyte, wherein the positive electrode comprises a positive electrode current collector layer and a positive electrode active material layer disposed on one or two surfaces of the positive electrode current collector layer and comprising a positive electrode active material layer composition, wherein the silicon-based negative electrode comprises a negative electrode current collector layer and a negative electrode active material layer disposed on one or two surfaces of the negative electrode current collector layer and comprising a negative electrode active material layer composition, wherein the negative electrode active material layer composition comprises a silicon-based active material, and the silicon-based active material comprises one or more selected from the group consisting of SiO x (x = 0), SiO x (0 < x < 2), SiC, and Si alloys, wherein the initial efficiency of the silicon-based negative electrode is 0.2% or more and 4% or less higher than that of the positive electrode, wherein the area ratio of the positive electrode active material layer to the negative electrode active material layer satisfies the range of 1:1.02 to 1:1.1, wherein the silicon-based negative electrode exhibits an asymmetric dimensional difference, wherein the full width of the silicon-based negative electrode is 1 mm or more wider than that of the positive electrode, and the full length of the silicon-based negative electrode is 2.5 mm or more longer than that of the positive electrode.

[0018] Beneficial Effects

[0019] The lithium secondary battery according to the present application can ensure that the battery has a high capacity and a high energy density by using a silicon-based negative electrode, and can also ensure fast charging performance by using a silicon-based active material with excellent capacity characteristics and forming a negative electrode thickness at the film level.

[0020] In particular, the initial efficiency between the positive electrode and the negative electrode, and the differences in area, full width, and full length between the positive electrode and the negative electrode can be adjusted, so as to avoid the interval with rapid volume change of the silicon-based negative electrode during discharge, thereby improving the cycle performance of the lithium secondary battery.

[0021] That is, when using a silicon-based active material (especially a pure Si active material), high capacity characteristics and energy density can be ensured. However, compared with the existing carbon-based active materials, the cycle performance deteriorates due to the volume expansion of the negative electrode caused by lithium migration during charge and discharge. However, the lithium secondary battery according to the present application solves the above problems by adjusting the above ratios even when using a negative electrode with a silicon-based active material as described above, and thus has the characteristic of ensuring life performance.

[0022] By adjusting the above conditions, the rapid volume change interval of the silicon-based active material is limited to minimize the damage to the pure Si particles, and the additional electrolyte decomposition is controlled to maintain reversible Li loss and the conductive network between the Si active materials, thereby controlling the amount of isolated lithium, resulting in improved cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A lithium secondary battery according to the present application is shown.

[0024] <Description of symbols>

[0025] 10: Negative electrode collector layer

[0026] 20: Negative electrode active material layer

[0027] 30: Diaphragm

[0028] 40: Positive electrode active material layer

[0029] 50: Positive electrode collector layer

[0030] 100: Negative electrode

[0031] 200: Positive DETAILED DESCRIPTION

[0032] Before describing the present invention, some terms are first defined.

[0033] In the present specification, when a part “includes,” “contains,” or “has” a constituent element, unless otherwise specifically stated, this does not mean that other constituent elements are excluded but that other constituent elements may be further included.

[0034] In this specification, "p to q" means a range of "p or more and q or less".

[0035] In this specification, "specific surface area" is measured by the BET method, specifically, calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77 K) using BELSORP-mini II available from BEL Japan, Inc. That is, in this application, the BET specific surface area may refer to the specific surface area measured by the above-mentioned measurement method.

[0036] In this specification, "Dn" refers to particle size distribution, and refers to the particle size at n% point in the cumulative distribution of the number of particles according to the particle size. That is, D50 is the particle size at 50% point in the cumulative distribution of the number of particles according to the particle size, D90 is the particle size at 90% point in the cumulative distribution of the number of particles according to the particle size, and D10 is the particle size at 10% point in the cumulative distribution of the number of particles according to the particle size. On the other hand, the particle size distribution can be measured using a laser diffraction method. Specifically, after the powder to be measured is dispersed in a dispersion medium, the resulting dispersion is introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), wherein the difference in the diffraction pattern according to the particle size is measured when the laser beam passes through the particle, and then the particle size distribution is calculated.

[0037] In the present specification, the description "a polymer includes a certain monomer as a monomer unit" means that the monomer participates in the polymerization reaction and is included in the polymer as a repeating unit. In the present specification, when a polymer includes a monomer, this should be interpreted as the same as the polymer including the monomer as a monomer unit.

[0038] In this specification, unless otherwise indicated as a "homopolymer", the term "polymer" is understood to be used in a broad sense including copolymers.

[0039] In this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are polystyrene-converted molecular weights measured by gel permeation chromatography (GPC) while using commercially available monodisperse polystyrene polymers (standard samples) with different polymerization degrees for measuring molecular weight as standard materials. In this specification, unless otherwise specifically stated, molecular weight refers to weight average molecular weight.

[0040] The embodiments of the present invention will be described in detail below with reference to the accompanying drawings so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the following description.

[0041] An exemplary embodiment of the present specification provides a lithium secondary battery, comprising: a positive electrode; a silicon-based negative electrode; a separator disposed between the positive electrode and the negative electrode; and an electrolyte, wherein the positive electrode comprises a positive electrode current collector layer and a positive electrode active material layer disposed on one surface or both surfaces of the positive electrode current collector layer and comprising a positive electrode active material layer composition, wherein the silicon-based negative electrode comprises a negative electrode current collector layer and a negative electrode active material layer disposed on one surface or both surfaces of the negative electrode current collector layer and comprising a negative electrode active material layer composition, wherein the negative electrode active material layer composition comprises a silicon-based active material, and the silicon-based active material comprises a selected from SiO x (x=0), SiO xOne or more of the group consisting of (0 < x < 2), SiC, and Si alloy, wherein the initial efficiency of the silicon-based negative electrode is 0.2% or more and 4% or less higher than the initial efficiency of the positive electrode, wherein the area ratio of the positive electrode active material layer to the negative electrode active material layer satisfies the range of 1:1.02 to 1:1.1, wherein the silicon-based negative electrode exhibits an asymmetric dimensional difference, wherein the full width of the silicon-based negative electrode is 1 mm or more wider than the full width of the positive electrode, and the full length of the silicon-based negative electrode is 2.5 mm or more longer than the full length of the positive electrode.

[0042] When using a silicon-based active material (especially a pure Si active material), high capacity characteristics and energy density can be ensured. However, compared with existing carbon-based active materials, the cycle performance deteriorates due to the volume expansion of the negative electrode caused by lithium migration during charge and discharge. However, the lithium secondary battery according to the present application solves the above problems by adjusting the above ratio even when a negative electrode using a silicon-based active material is applied as described above, and thus has the characteristic of ensuring life performance.

[0043] Figure 1 It is a diagram showing the laminated structure of a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, the negative electrode 100 can be seen, which includes a negative electrode active material layer 20 on one surface of the negative electrode current collector layer 10, and the positive electrode 200 can be seen, which includes a positive electrode active material layer 40 on one surface of the positive electrode current collector layer 50, and the negative electrode 100 and the positive electrode 200 for the lithium secondary battery are formed into a laminated structure with a separator 30 interposed therebetween.

[0044] In an exemplary embodiment of the present application, a lithium secondary battery is provided, wherein the initial efficiency of the silicon-based negative electrode is 0.2% or more and 4% or less higher than the initial efficiency of the positive electrode.

[0045] In the present application, the method for measuring the initial efficiency of the positive electrode is as follows. After manufacturing a lithium coin half-cell using the positive electrode and the counter electrode according to the present application, the lithium coin half-cell is charged at a current density of 0.45 mAh / cm 2 or less (or 0.2 C or less) to a voltage of 4.3 V under constant current, and then the charging is completed under constant voltage when the current density reaches 1 / 10 of the constant current, which is defined as the first charging capacity. After standing for 1 hour, the lithium coin half-cell is again discharged at a current density of 0.45 mAh / cm 2 or less (or 0.2 C or less), and the capacity when reaching 3.0 V is defined as the first discharge capacity. In this case, the initial efficiency of the positive electrode is calculated as the first discharge capacity / the first charging capacity × 100 (%).

[0046] In the present application, the method for measuring the initial efficiency of the negative electrode is as follows. After a lithium coin half-cell is manufactured using the negative electrode and the counter electrode according to the present application, the lithium coin half-cell is charged at a constant current of 0.45 mAh / cm 2 The battery was discharged at a current density of less than 0.2 C to a voltage of 0.005 V, and then the discharge was completed at a current density of 1 / 20 of the constant current under constant voltage, which was defined as the first discharge capacity. After standing for 1 hour, the lithium coin half-cell was charged at a constant current of 0.45 mAh / cm 2 The negative electrode is charged at a rate of 1.5 V or less (or 0.2 C or less), and the capacity when it reaches 1.5 V is defined as the first charge capacity. In this case, the initial efficiency of the negative electrode is calculated as the first charge capacity / first discharge capacity × 100 (%).

[0047] In an exemplary embodiment of the present application, a lithium secondary battery is provided, wherein the area ratio of the positive electrode active material layer to the negative electrode active material layer satisfies the range of 1:1.02 to 1:1.1, and wherein the silicon-based negative electrode exhibits an asymmetric size difference, wherein the full width of the silicon-based negative electrode is more than 1 mm larger than the full width of the positive electrode, and the full length of the silicon-based negative electrode is more than 2.5 mm larger than the full length of the positive electrode.

[0048] In an exemplary embodiment of the present application, the area ratio of the positive electrode active material layer to the negative electrode active material layer may satisfy the range of 1:1.02 to 1:1.1, and the silicon-based negative electrode may exhibit an asymmetric size difference, wherein the full width of the silicon-based negative electrode is greater than the full width of the positive electrode by more than 1 mm, preferably more than 1.5 mm and less than 10 mm, preferably less than 5 mm.

[0049] In an exemplary embodiment of the present application, the area ratio of the positive electrode active material layer to the negative electrode active material layer may satisfy the range of 1:1.02 to 1:1.1, and the silicon-based negative electrode may exhibit an asymmetric size difference, wherein the full width of the silicon-based negative electrode is greater than the full width of the positive electrode by more than 2.5 mm or more than 2.7 mm and less than 15 mm, preferably less than 8 mm, and specifically less than 5 mm.

[0050] In an exemplary embodiment of the present application, a lithium secondary battery is provided, wherein the silicon-based negative electrode exhibits an asymmetric size difference, wherein the full width of the silicon-based negative electrode is more than 1% larger than the full width of the positive electrode, and the full length of the silicon-based negative electrode is more than 2% larger than the full length of the positive electrode.

[0051] In another exemplary embodiment, a lithium secondary battery is provided, wherein the silicon-based negative electrode exhibits an asymmetric size difference, wherein the full width of the silicon-based negative electrode is greater than 1% and less than 10% greater than the full width of the positive electrode, and the full length of the silicon-based negative electrode is greater than 2% and less than 15% greater than the full length of the positive electrode.

[0052] In another exemplary embodiment, the full width of the silicon-based negative electrode may be greater than the full width of the positive electrode by more than 1% and less than 10% or more than 1% and less than 8%, and the full length of the silicon-based negative electrode may be greater than the full length of the positive electrode by more than 2% and less than 15% or more than 2% and less than 10%.

[0053] When the above range is met, the irreversible capacity of the positive electrode is appropriate compared to the negative electrode, so the use of the negative electrode can be limited. In addition, the battery performance capacity is appropriate, so the improvement effect on the SOC-restricted cycle performance is excellent. That is, in a lithium secondary battery, if the area ratio of the positive electrode active material layer to the negative electrode active material layer is lower than the above range, the irreversible capacity of the positive electrode increases compared to the negative electrode, so there is no restriction on the use of the negative electrode, and if the area ratio is higher than the above range, the battery performance capacity decreases, so the improvement effect on the SOC-restricted cycle performance cannot be obtained.

[0054] In an exemplary embodiment of the present application, the full length may refer to a length in a machine direction (MD), and the full width may refer to a length in a transverse direction (TD).

[0055] The positive electrode, the negative electrode, the electrolyte, and the separator included in the lithium secondary battery will be described below, respectively.

[0056] According to the present application, the silicon-based negative electrode may include a negative electrode current collector layer and a negative electrode active material layer disposed on one surface or both surfaces of the negative electrode current collector layer and including a negative electrode active material layer composition.

[0057] The thickness of the negative electrode collector layer is generally 1 μm to 100 μm. There is no particular limitation on this negative electrode collector as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel each surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode collector layer may have fine concave-convex formed on the surface to enhance the binding force with the negative electrode active material, and may be used in various forms, such as a film, a sheet, a foil, a net, a porous body, a foam or a non-woven fabric.

[0058] However, the thickness may be variously changed depending on the type and purpose of the negative electrode used, and is not limited thereto.

[0059] In an exemplary embodiment of the present application, the negative electrode active material layer may include a negative electrode active material layer composition, and the negative electrode active material layer composition may include a silicon-based active material.

[0060] In an exemplary embodiment of the present application, the negative electrode active material layer may include a negative electrode active material layer composition, and the negative electrode active material layer composition may include one or more selected from the group consisting of a silicon-based active material, a negative electrode conductive material, and a negative electrode binder.

[0061] In an exemplary embodiment of the present application, the negative electrode active material layer may include a negative electrode active material layer composition, and the negative electrode active material layer composition may include: a silicon-based active material; a negative electrode conductive material; and a negative electrode binder.

[0062] In an exemplary embodiment of the present application, the silicon-based active material may include one or more selected from the group consisting of SiO x (x = 0), SiO x (0 < x < 2), SiC, and Si alloy.

[0063] In an exemplary embodiment of the present application, the silicon-based active material may include one or more selected from the group consisting of SiO x (x = 0), SiO x (0 < x < 2), and metal impurities, and relative to 100 parts by weight of the silicon-based active material, the content of SiO x (x = 0) may be 70 parts by weight or more.

[0064] In another exemplary embodiment, relative to 100 parts by weight of the silicon-based active material, the content of SiO x (x = 0) may be 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, and may be 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.

[0065] In an exemplary embodiment of the present application, for the silicon-based active material, pure silicon (Si) may be particularly used as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material may mean that relative to a total of 100 parts by weight of the silicon-based active material, the content of pure Si particles (SiO x (x = 0)) not combined with other particles or elements is within the above range.

[0066] Note that the average particle size (D50) of the silicon-based active material of the present invention may be 3 μm to 15 μm, specifically 4 μm to 13 μm, and more specifically 4.5 μm to 11 μm. If the average particle size is less than 3 μm, the specific surface area of ​​the particles is excessively increased, resulting in an excessive increase in the viscosity of the negative electrode slurry. Therefore, the particles constituting the negative electrode slurry cannot be dispersed smoothly. In addition, if the size of the silicon-based active material is too small, the contact area between the silicon particles and the conductive material is reduced due to the composite composed of the conductive material and the binder in the negative electrode slurry, thereby increasing the possibility of disconnection of the conductive network, thereby reducing the capacity retention rate. On the other hand, if the average particle size is greater than 10 μm, there are too large silicon particles, making the negative electrode surface rough, resulting in uneven current density during charge and discharge. In addition, if the silicon particles are too large, the phase stability of the negative electrode slurry becomes unstable, thereby reducing processability. As a result, the capacity retention rate of the battery is reduced.

[0067] In an exemplary embodiment of the present application, the silicon-based active material generally has a characteristic BET specific surface area. The BET specific surface area of ​​the silicon-based active material is preferably 0.01 m 2 / g to 150.0 m 2 / g, more preferably 0.1m 2 / g to 100.0 m 2 / g, particularly preferably 0.2 m 2 / g to 80.0 m 2 / g, and most preferably 0.2 m 2 / g to 18.0 m 2 / g. The BET specific surface area is measured according to DIN 66131 (using nitrogen).

[0068] In an exemplary embodiment of the present application, the silicon-based active material may be present, for example, in a crystalline form or an amorphous form, preferably non-porous. The silicon particles are preferably spherical or fragmentary particles. Alternatively but less preferably, the silicon particles may also have a fibrous structure or be present in the form of a silicon-containing film or coating.

[0069] In an exemplary embodiment of the present application, the content of the silicon-based active material may be 60 parts by weight or more relative to 100 parts by weight of the negative electrode active material layer composition.

[0070] In another exemplary embodiment, the content of the silicon-based active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, and may be 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 80 parts by weight or less, relative to 100 parts by weight of the negative electrode active material layer composition.

[0071] The negative electrode active material layer composition according to the present application uses a specific negative electrode conductive material and a negative electrode binder, and even when a silicon-based active material with a significantly high capacity within the above range is used, the volume expansion rate during charge and discharge can be controlled. Therefore, even when the silicon-based active material is within the above range, the negative electrode active material layer composition does not reduce the performance of the negative electrode, and has excellent output characteristics during charge and discharge.

[0072] In an exemplary embodiment of the present application, the silicon-based active material may have a non-spherical shape, and the sphericity (circularity) thereof is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.

[0073] In the present application, the sphericity is determined by the following Formula 1, where A is the area and P is the boundary line.

[0074] [Formula 1]

[0075] 4πA / P 2

[0076] In the related art, only graphite compounds are usually used as negative electrode active materials. However, in recent years, with the increasing demand for high-capacity batteries, attempts to mix silicon-based compounds to increase capacity have increased. However, the silicon-based compounds have the following limitations: the volume expands rapidly during the charge and discharge process, resulting in damage to the conductive path formed in the negative electrode active material layer, thereby deteriorating the performance of the battery.

[0077] Therefore, in an exemplary embodiment of the present application, the negative electrode active material layer composition may include a negative electrode conductive material and a negative electrode binder. That is, the negative electrode conductive material plays a role in ensuring a conductive path, and the binder plays a role in retaining the negative electrode conductive material during charge and discharge.

[0078] In an exemplary embodiment of the present application, the negative electrode conductive material may include one or more selected from the group consisting of a point-shaped conductive material, a planar conductive material, and a linear conductive material.

[0079] In an exemplary embodiment of the present application, the dot-shaped conductive material refers to a conductive material that can be used to improve the conductivity of the negative electrode, form conductivity without causing chemical changes, and has a circular or dot-shaped shape. Specifically, the dot-shaped conductive material can be selected from one or more of the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and preferably includes carbon black in terms of high conductivity and excellent dispersibility.

[0080] In an exemplary embodiment of the present application, the BET specific surface area of ​​the dot-shaped conductive material may be 40 m 2 / g and above 70 m 2 / g or less, preferably 45 m 2 / g and above 65 m 2 / g or less, more preferably 50 m 2 / g or more and 60m 2 / g or less.

[0081] In an exemplary embodiment of the present application, the particle size of the dot-shaped conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 40 nm to 60 nm.

[0082] In an exemplary embodiment of the present application, the conductive material may include a planar conductive material.

[0083] The planar conductive material refers to a conductive material that improves conductivity by increasing the surface contact between silicon particles in the negative electrode and is used to suppress disconnection of the conductive path due to volume expansion. The planar conductive material can be a plate-shaped conductive material or a bulk-type conductive material.

[0084] In an exemplary embodiment of the present application, the planar conductive material may include one or more selected from the group consisting of plate-like graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate-like graphite.

[0085] In an exemplary embodiment of the present application, the average particle size (D50) of the planar conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 4 μm to 5 μm. When the above range is met, sufficient particle size does not cause excessive increase in viscosity of the negative electrode slurry, making it easy to disperse. Therefore, when the same equipment and time are used for dispersion, the dispersion effect is excellent.

[0086] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the planar conductive material has a D10 of 0.5 μm to 1.5 μm, a D50 of 4.0 μm to 5.0 μm, and a D90 of 7.0 μm to 15.0 μm.

[0087] In an exemplary embodiment of the present application, for the planar conductive material, a high specific surface area planar conductive material having a high BET specific surface area, or a low specific surface area planar conductive material may be used.

[0088] In an exemplary embodiment of the present application, for the planar conductive material, a planar conductive material with a high specific surface area or a planar conductive material with a low specific surface area can be used without restriction. However, in particular, the planar conductive material according to the present application can be affected by dispersion to a certain extent in terms of electrode performance, so that it is particularly preferred to use a planar conductive material with a low specific surface area that does not cause problems in terms of dispersion.

[0089] In an exemplary embodiment of the present application, the BET specific surface area of ​​the planar conductive material may be 1 m 2 / g or above.

[0090] In another exemplary embodiment, the BET specific surface area of ​​the planar conductive material may be 1 m 2 / g and above 500 m 2 / g or less, preferably 5 m 2 / g and above 300 m 2 / g or less, more preferably 5 m 2 / g and above 250 m 2 / g or less.

[0091] In another exemplary embodiment, the planar conductive material is a planar conductive material with a high specific surface area, and the BET specific surface area may satisfy 50 m 2 / g and above 500 m 2 / g or less, preferably 80 m 2 / g and above 300 m 2 / g or less, more preferably 100 m 2 / g and above 250 m 2 / g or less.

[0092] In another exemplary embodiment, the planar conductive material is a planar conductive material with a low specific surface area, and the BET specific surface area may satisfy 1 m 2 / g and above 40 m 2 / g or less, preferably 5 m 2 / g or more and 30 m 2 / g or less, more preferably 5 m 2 / g and above 25 m 2 / g or less.

[0093] Other conductive materials may include linear conductive materials, such as carbon nanotubes. The carbon nanotubes may be bundle-type carbon nanotubes. The bundle-type carbon nanotubes may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle-type" herein refers to a secondary shape in which a plurality of carbon nanotube units are arranged side by side or are wound in a bundle or rope-like manner in a manner that the longitudinal axis orientation of the carbon nanotube units is substantially the same. The carbon nanotube unit has a cylindrical graphite sheet with a nanometer-sized diameter and has an sp2 bonding structure. In this case, the characteristics of a conductor or a semiconductor may be exhibited according to the curling angle and structure of the graphite sheet. Compared with the wound carbon nanotubes, the bundle-type carbon nanotubes can be more evenly dispersed during the manufacture of the negative electrode, and can more smoothly form a conductive network in the negative electrode, thereby improving the conductivity of the negative electrode.

[0094] In an exemplary embodiment of the present application, the negative electrode conductive material may include a linear conductive material, and the linear conductive material may be a carbon nanotube.

[0095] In an exemplary embodiment of the present application, the carbon nanotube may be SWCNT or / and MWCNT. When the linear conductive material is SWCNT, the length of the SWCNT may be 0.5 μm to 100 μm, preferably 1 μm to 80 μm.

[0096] In an exemplary embodiment of the present application, the content of the negative electrode conductive material may be 5 parts by weight or more and 40 parts by weight or less relative to 100 parts by weight of the negative electrode active material layer composition.

[0097] In another exemplary embodiment, the content of the negative electrode conductive material may be 5 parts by weight or more and 40 parts by weight or less, preferably 5 parts by weight or more and 30 parts by weight or less, and more preferably 5 parts by weight or more and 25 parts by weight or less, relative to 100 parts by weight of the negative electrode active material layer composition.

[0098] In an exemplary embodiment of the present application, the negative electrode conductive material may include a planar conductive material and a linear conductive material, and a ratio of the planar conductive material to the linear conductive material may satisfy 1:0.001 to 1:0.3.

[0099] In an exemplary embodiment of the present application, since the negative electrode conductive material comprises a planar conductive material and a linear conductive material and satisfies the above-mentioned composition and proportion respectively, the life characteristics of the existing lithium secondary battery are not significantly affected, and the number of sites at which the battery can be charged and discharged is increased, so that the output characteristics at a high C rate are excellent.

[0100] The negative electrode conductive material according to the present application has a completely different structure from the conductive material applied to the positive electrode. That is, the negative electrode conductive material according to the present application is used to maintain contact between the silicon-based active materials in which the electrode volume expansion caused by charging and discharging is very large, while the positive electrode conductive material is used to play a buffering role during rolling while imparting a certain conductivity, and is completely different from the negative electrode conductive material of the present invention in terms of structure and function.

[0101] In addition, the negative electrode conductive material according to the present application is applied to the silicon-based active material and has a completely different structure from the conductive material applied to the graphite-based active material. That is, since the conductive material used for the electrode with the graphite-based active material simply has smaller particles than the active material, the conductive material has the characteristics of improving the output characteristics and imparting a certain conductivity, and is completely different from the negative electrode conductive material applied together with the silicon-based active material in the present invention in terms of structure and function.

[0102] In an exemplary embodiment of the present application, the plate-shaped conductive material used as the above-mentioned negative electrode conductive material has a different structure and function from the carbon-based active material generally used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and refers to a material processed into a spherical or dot-like shape for use to promote lithium ion storage and release.

[0103] On the other hand, the plate-like conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape, and may be in the form of plate-like graphite. That is, the plate-like conductive material is a material contained in order to maintain a conductive path in the negative electrode active material layer, and refers to a material that ensures a conductive path in a planar shape inside the negative electrode active material layer, rather than a material that plays a role in storing and releasing lithium.

[0104] That is, in the present application, using plate-like graphite as a conductive material means processing graphite into a planar or plate-like shape and using it as a material that ensures a conductive path rather than a material that plays a role in storing or releasing lithium. In this case, the negative electrode active material contained together has high capacity characteristics in terms of storing and releasing lithium, and plays a role in storing and releasing all lithium ions transferred from the positive electrode.

[0105] On the other hand, in the present application, using a carbon-based active material as an active material means that the carbon-based active material is processed into a dot-like or spherical shape and used as a material for storing or releasing lithium.

[0106] In an exemplary embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, and the above materials in which hydrogen is replaced by Li, Na, Ca, etc., and may also include various copolymers thereof.

[0107] The negative electrode binder according to an exemplary embodiment of the present application is used to retain the silicon-based active material and the negative electrode conductive material so as to prevent the negative electrode structure from being distorted and deformed when the silicon-based active material expands and relaxes. As long as such a role is met, all conventional binders can be applied. Specifically, an aqueous binder can be used, and more specifically, a PAM-based binder can be used.

[0108] In an exemplary embodiment of the present application, the content of the negative electrode binder may be 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, and may be 5 parts by weight or more and 8 parts by weight or more, relative to 100 parts by weight of the negative electrode active material layer composition.

[0109] Compared with the existing carbon-based negative electrode, when using a Si-based negative electrode, the aqueous binder is applied according to the above weight portion, so that a dot-shaped conductive material with a low functional group content can be used. In addition, the above characteristics make the dot-shaped conductive material hydrophobic and have excellent bonding strength between the conductive material / binder.

[0110] In an exemplary embodiment of the present application, the silicon-based negative electrode may be formed by coating a negative electrode slurry including the negative electrode active material layer composition on one surface or both surfaces of the negative electrode current collector layer.

[0111] In an exemplary embodiment of the present application, the negative electrode slurry may include a negative electrode active material layer composition and a slurry solvent.

[0112] In an exemplary embodiment of the present application, the solid content of the negative electrode slurry may satisfy a range of 5% or more and 40% or less.

[0113] In another exemplary embodiment, the solid content of the negative electrode slurry may satisfy a range of 5% to 40% both inclusive, preferably 7% to 35% both inclusive, and more preferably 10% to 30% both inclusive.

[0114] The solid content of the negative electrode slurry may refer to the content of the negative electrode composition contained in the negative electrode slurry, and may refer to the content of the negative electrode composition relative to 100 parts by weight of the negative electrode slurry.

[0115] When the solid content of the negative electrode slurry satisfies the above range, the viscosity is appropriate during the formation of the negative electrode active material layer, thereby minimizing the aggregation of particles of the negative electrode composition, thereby effectively forming the negative electrode active material layer.

[0116] In an exemplary embodiment of the present application, the slurry solvent may be used without limitation as long as it can disperse the above-mentioned negative electrode composition, and specifically, water or NMP may be used.

[0117] In an exemplary embodiment of the present application, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less.

[0118] In another exemplary embodiment, the porosity of the negative electrode active material layer may satisfy the range of 10% to 60% both inclusive, preferably 20% to 50% both inclusive, and more preferably 30% to 45% both inclusive.

[0119] The porosity varies depending on the composition and content of the silicon-based active material, conductive material and binder contained in the negative electrode active material layer, and in particular, when the silicon-based active material and conductive material according to the present application are contained in a specific composition and content, the above range is satisfied, so that the electrode has conductivity and resistance within an appropriate range.

[0120] In an exemplary embodiment of the present application, the positive electrode includes a positive electrode collector layer and a positive electrode active material layer provided on one surface or both surfaces of the positive electrode collector layer and including a positive electrode active material layer composition.

[0121] In an exemplary embodiment of the present application, the positive electrode active material layer may include a positive electrode active material layer composition, and the positive electrode active material layer composition may include one or more selected from the group consisting of a positive electrode active material, a positive electrode conductive material, and a positive electrode binder.

[0122] In the positive electrode, there is no particular restriction on the positive electrode collector layer, as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, aluminum or stainless steel treated with carbon, nickel, titanium, silver, etc., can be used. In addition, the thickness of the positive electrode collector layer can generally be 1 to 500 μm, and the surface of the positive electrode collector layer can be formed with fine concave and convex to enhance the adhesion with the positive electrode active material. For example, the positive electrode collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0123] In an exemplary embodiment of the present application, a lithium secondary battery is provided, wherein the thickness of each of the positive electrode collector layer and the negative electrode collector layer is 1 μm or more and 100 μm or less, and the thickness of each of the positive electrode active material layer and the negative electrode active material layer is 20 μm or more and 500 μm or less.

[0124] In an exemplary embodiment of the present application, a lithium secondary battery is provided, wherein the positive electrode active material layer composition contains a positive electrode active material, the positive electrode active material contains one or more selected from the group consisting of a large-particle positive electrode active material having a center particle size (D50) of 9 μm or more and a small-particle positive electrode active material having a center particle size (D50) of 10 μm or less, and the content of the large-particle positive electrode active material is 45 parts by weight or more and 100 parts by weight or less relative to 100 parts by weight of the positive electrode active material.

[0125] In another exemplary embodiment, the positive electrode active material may include one or more selected from the group consisting of a large-particle positive electrode active material having a central particle size (D50) of 10 μm or more and a small-particle positive electrode active material having a central particle size (D50) of 10 μm or less, and the content of the large-particle positive electrode active material may be 45 parts by weight or more and 100 parts by weight or less, preferably 46 parts by weight or more and 100 parts by weight or less, and more preferably 48 parts by weight or more and 100 parts by weight or less, relative to 100 parts by weight of the positive electrode active material.

[0126] In this case, the description "the content of the large-particle-size positive electrode active material is 100 parts by weight" may mean that the positive electrode active material is composed of only the large-particle-size positive electrode active material.

[0127] In an exemplary embodiment of the present application, a lithium secondary battery is provided, wherein the positive electrode active material comprises a large-particle size positive electrode active material and a small-particle size positive electrode active material, wherein the average particle size (D50) of the large-particle size positive electrode active material is greater than 9 μm and less than 15 μm, and the average particle size (D50) of the small-particle size positive electrode active material is greater than 3 μm and less than 6 μm.

[0128] In an exemplary embodiment of the present application, a lithium secondary battery is provided, wherein the initial efficiency of the positive electrode is 90% or less, more specifically, the initial efficiency of the positive electrode may satisfy 80% or more, more specifically, satisfy 85% or more.

[0129] As described above, when the large-particle-size positive electrode active material is included in the above range, the above initial efficiency of the positive electrode can be achieved. That is, by keeping the initial efficiency of the positive electrode lower than the initial efficiency of the negative electrode, the interval of silicon accompanied by rapid volume change is not used during discharge, thereby improving the cycle performance.

[0130] In an exemplary embodiment of the present application, the central particle size (D50) of the large-particle-size positive electrode active material may satisfy a range of 9 μm or more or 9.3 μm or more and 20 μm or less, preferably 13 μm or less.

[0131] In an exemplary embodiment of the present application, the center particle size (D50) of the small particle active material may satisfy the range of 10 μm or less, 8 μm or less, specifically 7 μm or less, more specifically 6 μm or less and 1 μm or more, preferably 3 μm or more.

[0132] Finally, according to the present invention, the initial efficiency of the positive electrode is adjusted by adjusting the weight portion of the large-particle positive electrode active material as described above, and accordingly, as described above, the area ratio, full width and full length of the positive electrode and the negative electrode are adjusted to produce an asymmetric size difference, thereby achieving the main purpose of the present invention, that is, being able to obtain the advantages of using a silicon-based negative electrode while being able to solve problems related to life characteristics.

[0133] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may include a material selected from the group consisting of LiNi x Co y Mn z O 2 (x+y+z=1), LiNi a Co b Mn c Al d O 2 (a+b+c+d=1), LiMn 2 O 4, LiNi 0.5 Mn 1.5 O 2 and LiM x Fe y PO 4 (M: transition metal, x + y = 1), and more than one of the group consisting of. In this case, the positive electrode active material is not limited thereto.

[0134] In an exemplary embodiment of the present application, a lithium secondary battery is provided, wherein the positive electrode active material is nickel cobalt manganese (NCM) oxide or nickel cobalt manganese aluminum (NCMA) oxide, and in the nickel cobalt manganese (NCM) oxide and nickel cobalt manganese aluminum (NCMA) oxide, among all metals other than lithium, the content of nickel contained is 50 mol% or more.

[0135] In another exemplary embodiment, the positive electrode active material may be nickel cobalt manganese (NCM) oxide or nickel cobalt manganese aluminum (NCMA) oxide, and in the nickel cobalt manganese (NCM) oxide and nickel cobalt manganese aluminum (NCMA) oxide, among all metals other than lithium, the content of nickel contained may be 50 mol% or more, preferably 55 mol% or more, more preferably 60 mol% or more, and most preferably 65 mol% or more. In addition, relative to all metals other than Li, the content of nickel (Ni) may be 95 mol% or less or 90 mol% or less.

[0136] When the content of nickel is less than the above range, the content of cobalt increases, thereby increasing the thermal stability. However, the capacity of the positive electrode active material is reduced, resulting in the problem that the positive electrode active material cannot be applied to an electrochemical device that requires high capacity.

[0137] On the other hand, within the above range, the higher the content of nickel, the higher the capacity characteristics that the lithium secondary battery containing it can exhibit. However, as the content of nickel increases, the content of cobalt and / or manganese relatively decreases, and therefore, the thermal stability may decrease. Therefore, when the content of nickel is within the above range, the efficiency of the lithium secondary battery according to the present application can be maximized.

[0138] In an exemplary embodiment of the present application, the nickel cobalt manganese (NCM) oxide can be represented as lithium nickel cobalt manganese oxide as follows. The lithium nickel cobalt manganese (NCM) oxide is composed of Li 1+x (Ni a Co b Mn c )O 2 (0.97 ≤ x ≤ 1.06, 0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), a Ni-Co-Mn ternary system positive electrode active material represented by Li 1+x (Nia Co b Mn c )O 4 (0.97 ≤ x ≤ 1.06, 0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2) represents the positive electrode active material of the Ni - Co - Mn ternary system, or a mixture thereof, which is a composite integrating the advantages such as the high capacity of nickel - containing oxides, the thermal stability of manganese - containing oxides, and the excellent electrochemical properties of cobalt - containing oxides. The lithium nickel cobalt manganese (NCM) oxide can be doped with a small amount of metal elements to an extent that meets the purpose of the present invention. For example, as a non - limiting example, by Li 1+x (Ni a Co b Mn c )O 2 (0.97 ≤ x ≤ 1.06, 0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1) or Li 1+x (Ni a Co b Mn c )O 4 (0.97 ≤ x ≤ 1.06, 0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2) represents the lithium nickel cobalt manganese (NCM) oxides represented by the positive electrode active material of the Ni - Co - Mn ternary system can each independently be doped with one or more metals selected from the group consisting of Na, K, Mg, Ca, Sr, Ni, Co, Ti, Al, Si, Sn, Mn, Cr, Fe, V, and Zr.

[0139] The amount of the metal doped into the lithium nickel cobalt manganese (NCM) can be within a range that does not significantly increase the positive electrode resistance. For example, based on each element, the doped metal in the lithium nickel cobalt manganese (NCM) oxide can be in the range of 10 to 1500 ppm, 50 to 1000 ppm, or 100 to 500 ppm, but is not limited thereto. As a non - limiting example, the lithium nickel cobalt manganese (NCM) oxide usually uses 2 to 3 elements as the doped metal, and based on each element, the amount of the doped metal may be several hundred ppm.

[0140] In an exemplary embodiment of the present application, in the nickel cobalt manganese (NCM) oxide, among all the metals other than lithium, the content of nickel contained can be 80 mol% or more, specifically 85 mol% or more, more specifically 88 mol% or more, and more specifically 93 mol% or more.

[0141] In Li 1+x (Ni a Co b Mn C )O2 In the formula represented by (0.97 ≤ x ≤ 1.06, 0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), the content of nickel can refer to the proportion of a contained. That is, in the case of a three-component system, it can refer to the proportion of nickel among nickel, cobalt, and manganese metals.

[0142] In an exemplary embodiment of the present application, nickel cobalt manganese aluminum (NCMA) oxide can be represented as lithium nickel cobalt manganese aluminum oxide as follows. The lithium nickel cobalt manganese aluminum (NCMA) oxide is composed of Li 1+x (Ni a Co b Mn C Al d )O 2 The positive electrode active material of the Ni - Co - Mn - Al four-component system represented by (0.97 ≤ x ≤ 1.06, 0 < a < 1, 0 < b < 1, 0 < c < 1, 0 < d < 1, a + b + c + d = 1), the positive electrode active material of the Ni - Co - Mn - Al four-component system composed of Li 1+x (Ni a Co b Mn C Al d )O 4 represented by (0.97 ≤ x ≤ 1.06, 0 < a < 2, 0 < b < 2, 0 < c < 2, 0 < d < 2, a + b + c + d = 2), or a mixture thereof, and is a composite that combines the advantages such as the high capacity of nickel-containing oxides, the thermal stability of manganese-containing oxides, and the excellent electrochemical properties of cobalt-containing oxides. The lithium nickel cobalt manganese aluminum (NCMA) oxide can be doped with a small amount of metal elements to an extent that meets the purpose of the present invention.

[0143] For example, as a non-limiting example, by Li 1+x (Ni a Co b Mn c Al d )O 2 represented by (0.97 ≤ x ≤ 1.06, 0 < a < 1, 0 < b < 1, 0 < c < 1, 0 < d < 1, a + b + c + d = 1) or Li 1+x (Ni a Co b Mn c Al d )O 4The nickel-cobalt-manganese-aluminum (NCMA) represented by the positive electrode active material of the Ni-Co-Mn-Al four-component system expressed as (0.97 ≤ x ≤ 1.06, 0 < a < 2, 0 < b < 2, 0 < c < 2, 0 < d < 2, a + b + c + d = 2) can each be independently doped with one or more metals selected from the group consisting of Na, K, Mg, Ca, Sr, Ni, Co, Ti, Al, Si, Sn, Mn, Cr, Fe, V, and Zr.

[0144] In an exemplary embodiment of the present application, in the nickel-cobalt-manganese-aluminum (NCMA) oxide, among all the metals other than lithium, the content of nickel contained can be 80 mol% or more, specifically 85 mol% or more, more specifically 88 mol% or more, and more specifically 93 mol% or more.

[0145] In the formula represented by Li 1+x (Ni a Co b Mn c Al d )O 2 (0.97 ≤ x ≤ 1.06, 0 < a < 1, 0 < b < 1, 0 < c < 1, 0 < d < 1, a + b + c + d = 1), the content of nickel can refer to the proportion of a contained. That is, in the case of the four-component system, the content of nickel can refer to the proportion of nickel among the nickel, cobalt, manganese, and aluminum metals.

[0146] In an exemplary embodiment of the present application, the average particle size (D50) of the positive electrode active material can be 5 μm to 20 μm, preferably 6 μm to 15 μm. That is, since the positive electrode active material contains large-particle-size positive electrode active material, the total average particle size can satisfy the above range.

[0147] In an exemplary embodiment of the present application, there is provided a lithium secondary battery, in which, relative to 100 parts by weight of the positive electrode active material layer composition, the content of the single-particle positive electrode active material is 90 parts by weight or more.

[0148] In another exemplary embodiment, relative to 100 parts by weight of the positive electrode active material layer composition, the content of the single-particle positive electrode active material can be 90 parts by weight or more, preferably 93 parts by weight or more, more preferably 95 parts by weight or more, and can be 99 parts by weight or less or 98 parts by weight or less.

[0149] The positive electrode active material layer can further contain a positive electrode conductive material and a positive electrode binder on the basis of containing the above single-particle positive electrode active material.

[0150] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation, as long as the positive electrode conductive material has electronic conductivity without causing chemical changes in the constituted battery. Specific examples may include graphite such as natural graphite and artificial graphite; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc., and any one thereof or a mixture of two or more thereof may be used.

[0151] Specifically, in one embodiment of the present application, a lithium secondary battery is provided, wherein the positive electrode conductive material comprises single-walled carbon nanotubes (SWCNTs) or multi-walled carbon nanotubes (MWCNTs), and its content is greater than 0.1 parts by weight and less than 2 parts by weight relative to 100 parts by weight of the positive electrode active material layer composition.

[0152] In another exemplary embodiment, the content of the positive electrode conductive material may be 0.1 parts by weight or more and 2 parts by weight or less, preferably 0.3 parts by weight or more and 1.5 parts by weight or less, and more preferably 0.5 parts by weight or more and 1.2 parts by weight or less, relative to 100 parts by weight of the positive electrode active material layer composition.

[0153] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof may be used.

[0154] In this case, the content of the positive electrode binder may be 0.1 parts by weight or more and 10 parts by weight or less, preferably 1 part by weight or more and 5 parts by weight or less, relative to 100 parts by weight of the positive electrode composition.

[0155] The diaphragm is used to separate the negative electrode from the positive electrode and provide a lithium ion migration path, wherein any diaphragm can be used as the diaphragm without particular limitation, as long as it is generally used for secondary batteries, in particular, it is preferred to use a diaphragm with high moisture retention capacity for electrolytes and low resistance to electrolyte ion migration. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminated structure of more than two layers thereof. In addition, conventional porous non-woven fabrics can be used, such as non-woven fabrics formed of high melting point glass fibers, polyethylene terephthalate fibers, etc. In addition, a coated diaphragm comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a diaphragm with a single-layer or multilayer structure can be selectively used.

[0156] In the present application, examples of the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten inorganic electrolyte that can be used to manufacture a lithium secondary battery, but are not limited thereto.

[0157] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.

[0158] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate or ethyl propionate can be used.

[0159] Especially, in the carbonate-based organic solvent, ethylene carbonate and propylene carbonate as cyclic carbonate are high viscosity organic solvents and can be preferably used, because their dielectric constant is high, thereby lithium salt is well dissociated. When cyclic carbonate is low in viscosity and straight-chain carbonates with low dielectric constant such as dimethyl carbonate and diethyl carbonate are mixed with suitable ratio and used, high conductivity electrolyte can be prepared, so such combination can be more preferred.

[0160] As the metal salt, a lithium salt which is a material easily dissolved in the non-aqueous electrolyte may be used, wherein as anions of the lithium salt, for example, one or more selected from the group consisting of: F- 、Cl - 、I - 、NO 3 - 、N(CN) 2 - 、BF 4 - 、ClO 4 - 、PF 6 - 、(CF 3 ) 2 PF 4 - 、(CF 3 ) 3 PF 3 - 、(CF 3 ) 4 PF 2 - 、(CF 3 ) 5 PF - 、(CF 3 ) 6 P - 、CF 3 SO 3 - 、CF 3 CF 2 SO 3 - 、(CF 3 SO 2 ) 2 N - 、(FSO 2 ) 2 N - 、CF 3 CF 2 (CF 3 ) 2 CO - 、(CF 3 SO 2 ) 2 CH - 、(SF 5 ) 3 C - 、(CF 3 SO 2 ) 3 C - 、CF 3 (CF 2 ) 7 SO 3 - 、CF 3CO 2 - , CH 3 CO 2 - 、SCN - and (CF 3 CF 2 SO 2 ) 2 N - .

[0161] In order to improve the life characteristics of the battery, inhibit the decrease of the battery capacity, improve the discharge capacity of the battery, etc., in addition to the above-mentioned electrolyte components, the electrolyte may further contain one or more additives, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme dimethyl ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0162] An exemplary embodiment of the present invention provides a battery module and a battery pack including the same, wherein the battery module includes the secondary battery as a unit cell. Since the battery module and the battery pack include secondary batteries having high capacity, high rate capability, and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0163] Mode for use in the present invention

[0164] Hereinafter, preferred embodiments will be provided for a better understanding of the present invention. It will be apparent to those skilled in the art that the embodiments are provided only to illustrate the present invention, and that various changes and variants are possible within the scope and technical concept of the present invention. Such changes and variants naturally fall within the scope of the claims contained herein.

[0165] <Preparation Example>

[0166] (1) Preparation of positive electrode

[0167] As the positive electrode active material, a positive electrode active material having the characteristics shown in the following Table 1 was used.

[0168]

[0169] In the above Table 1, each part by weight corresponds to part by weight relative to 100 parts by weight of the entire positive electrode active material.

[0170] In Table 1 above, the large-particle-size positive electrode active material A is Li(Ni a Co b Mn c ) 2 In the single-particle positive electrode active material, lithium (Li) and oxygen (O 2 ) satisfies the ratio of Ni:Co:Mn=93:5:2 (a:b:c=0.93:0.05:0.02), and the center particle size (D50) is 11 μm.

[0171] In Table 1 above, the small-particle positive electrode active material A is Li(Ni a Co b Mn c ) 2 In the single-particle positive electrode active material, lithium (Li) and oxygen (O 2 ) satisfies the ratio of Ni:Co:Mn=93:5:2 (a:b:c=0.93:0.05:0.02), and the center particle size (D50) is 4 μm.

[0172] In Table 1 above, the large-particle-size positive electrode active material B is Li(Ni a Co b Mn c ) 2 In the single-particle positive electrode active material, lithium (Li) and oxygen (O 2 ) satisfies the ratio of Ni:Co:Mn=93:5:2 (a:b:c=0.93:0.05:0.02), and the central particle size (D50) is 11 μm, and corresponds to a single-particle active material in which the primary particle is one particle block.

[0173] The positive electrode active material, positive electrode conductive material (LB. CNT) and binder (PVdF, KF9700) were added to a solvent (N-methylpyrrolidone, NMP) at a weight ratio of 97.96:0.8:1.24 to prepare a positive electrode slurry. The positive electrode slurry was applied to an aluminum (Al) film having a thickness of 25 μm as a positive electrode current collector, dried, and then rolled to prepare a positive electrode.

[0174] (2) Preparation of negative electrode

[0175] A negative electrode active material layer composition was prepared using Si (average particle size (D50): 5 μm) as a silicon-based active material, a first conductive material, a second conductive material, and polyacrylamide as a binder in a weight ratio of 80:9.6:0.4:10. A negative electrode slurry (solid concentration: 28 wt %) was prepared by adding the composition to distilled water as a solvent for forming a negative electrode slurry.

[0176] The first conductive material is plate-like graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the second conductive material is carbon nanotubes.

[0177] As a mixing method, the first conductive material, the second conductive material, the binder, and water were dispersed using a homomixer at 2500 rpm for 30 minutes, the active material was added thereto, and the resulting mixture was dispersed at 2500 rpm for 30 minutes to manufacture slurry.

[0178] The negative electrode slurry was prepared at 3.00 mg / cm 2 The negative electrode was coated on both surfaces of a copper current collector (thickness: 15 μm) as a negative electrode current collector, and then rolled and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 23 μm).

[0179] (3) Preparation of secondary batteries

[0180] An electrode assembly was prepared by inserting a compression-resistant thin film separator (PE 12 μm) having a ceramic coating 3 μm / 3 μm between the positive electrode and the negative electrode. After the electrode assembly was placed inside a case, an electrolyte was injected into the case to prepare a lithium secondary battery having the characteristics shown in Table 2 below.

[0181]

[0182] Experimental Example 1: Calculation of Energy Density

[0183] For the lithium secondary batteries prepared in Example 3 and Comparative Examples 3 and 4, for a battery size of 102×548, assuming the negative and positive electrode sizes under the corresponding conditions, the energy density of a medium-to-large battery with 40 stacks is calculated, and the results are shown in Table 3. According to the high energy density Si battery design standard, the feasibility of meeting the 800 Wh / L design is represented by O and ×.

[0184]

[0185] Experimental Example 2: Evaluation of Pouch Battery Life

[0186] For the lithium secondary batteries prepared in Examples 1 to 3 and Comparative Examples 1, 2 and 5, an electrochemical charge and discharge device was used to evaluate the life and capacity retention. The secondary batteries were subjected to an in-situ cycle test at 4.2-3.2 V 1 C / 1 C, and during the test, 1 C / 1 C charge and discharge (4.2-3.2 V) was performed every 50 cycles to measure the capacity retention, and the results are listed in Table 4.

[0187] Capacity retention rate (%) = {(discharge capacity at the Nth cycle) / (discharge capacity at the first cycle)}×100

[0188] After the evaluation was completed, the battery was disassembled to check whether Li plating occurred on the tab or electrode side. The results are shown in Table 4 below.

[0189]

[0190] As can be seen in the above-mentioned Experimental Examples 1 and 2, it can be confirmed that the lithium secondary battery according to the present application can realize a battery with high capacity and high energy density to be ensured by using a silicon-based negative electrode, and in particular, the initial efficiency between the positive electrode and the negative electrode and the difference in area, full width and full length between the positive electrode and the negative electrode can be adjusted, so that the interval of rapid volume change associated with the silicon-based negative electrode is not used during discharge, thereby improving the cycle performance of the lithium secondary battery.

[0191] That is, it can be confirmed that by adjusting the above conditions, the rapid volume change range of the silicon-based active material is limited to minimize the damage to the pure Si particles, and the additional electrolyte decomposition is controlled to maintain reversible Li loss and the conductive network between the Si active materials, thereby controlling the amount of isolated lithium, resulting in improved cycle performance.

[0192] As can be seen in Table 3, it can be confirmed that the energy density of the lithium secondary battery according to Example 3 of the present application is formed at a high level compared with Comparative Examples 3 and 4.

[0193] As can be seen in Table 4, it can be confirmed that the life performance of the lithium secondary batteries according to Examples 1 to 3 of the present application is higher than that of Comparative Examples 1 and 2. In addition, in the case of Comparative Example 5 in which the values ​​of the full width and full length of the negative electrode and the positive electrode are different from those of the present application, the life performance is similar to that of the embodiments, but decomposition causes Li precipitation on the tabs or electrode sides, thereby causing problems in the operation of the lithium secondary battery.

Claims

1. A lithium secondary battery comprising: positive electrode; Silicon-based negative electrode; A separator disposed between the positive electrode and the negative electrode; and Electrolytes, wherein the positive electrode comprises a positive electrode current collector layer and a positive electrode active material layer disposed on one surface or both surfaces of the positive electrode current collector layer and comprising a positive electrode active material layer composition, The silicon-based negative electrode comprises a negative electrode current collector layer and a negative electrode active material layer disposed on one surface or both surfaces of the negative electrode current collector layer and comprising a negative electrode active material layer composition, wherein the negative electrode active material layer composition includes a silicon-based active material, and the silicon-based active material includes one or more selected from the group consisting of SiO x (x = 0), SiO x (0 < x < 2), SiC, and Si alloys, The initial efficiency of the silicon-based negative electrode is higher than the initial efficiency of the positive electrode by 0.2% or more and 4% or less, wherein the area ratio of the positive electrode active material layer to the negative electrode active material layer satisfies the range of 1:1.02 to 1:1.1, and The silicon-based negative electrode exhibits an asymmetric size difference, wherein the full width of the silicon-based negative electrode is more than 1 mm larger than the full width of the positive electrode, and the full length of the silicon-based negative electrode is more than 2.5 mm larger than the full length of the positive electrode.

2. The lithium secondary battery according to claim 1, wherein the silicon-based active material comprises one or more selected from the group consisting of SiO x (x = 0), SiO x (0 < x < 2), and metal impurities, and the content of SiO x (x = 0) is 70 parts by weight or more with respect to 100 parts by weight of the silicon-based active material. 3 . The lithium secondary battery according to claim 1 , wherein the content of the silicon-based active material is 60 parts by weight or more relative to 100 parts by weight of the negative electrode active material layer composition.

4. The lithium secondary battery according to claim 1, wherein the positive electrode active material layer composition comprises a positive electrode active material, wherein the positive electrode active material comprises one or more selected from the group consisting of a large-particle positive electrode active material having a center particle diameter (D50) of 9 μm or more and a small-particle positive electrode active material having a center particle diameter (D50) of 10 μm or less, The content of the large-particle-size positive electrode active material is 45 parts by weight or more and 100 parts by weight or less relative to 100 parts by weight of the positive electrode active material. 5 . The lithium secondary battery according to claim 1 , wherein the initial efficiency of the positive electrode is 90% or less.

6. The lithium secondary battery according to claim 1, wherein the positive electrode active material comprises a material selected from the group consisting of LiNi x Co y Mn z O2(x+y+z=1), LiNi a Co b Mn c Al d O2 (a+b+c+d=1), LiMn2O4, LiNi 0.5 Mn 1.5 O2 and LiM x Fe y One or more selected from the group consisting of PO4 (M: transition metal, x+y=1).

7. The lithium secondary battery according to claim 4, wherein the positive electrode active material is nickel cobalt manganese (NCM) oxide or nickel cobalt manganese aluminum (NCMA) oxide, and The nickel-cobalt-manganese (NCM) oxide and the nickel-cobalt-manganese-aluminum (NCMA) oxide contain nickel in an amount of 50 mol % or more in all metals except lithium.

8. The lithium secondary battery according to claim 4, wherein the positive electrode active material comprises a large-particle-size positive electrode active material and a small-particle-size positive electrode active material, wherein the average particle size (D50) of the large-particle-size positive electrode active material is 9 μm or more and 15 μm or less, and The small-particle-size positive electrode active material has an average particle size (D50) of 3 μm or more and 6 μm or less. 9 . The lithium secondary battery according to claim 4 , wherein the average particle diameter (D50) of the positive electrode active material is 5 μm or more and 20 μm or less. 10 . The lithium secondary battery according to claim 4 , wherein the content of the positive electrode active material is 90 parts by weight or more relative to 100 parts by weight of the positive electrode active material layer composition.

11. The lithium secondary battery according to claim 1, wherein the thickness of the positive electrode current collector layer and the negative electrode current collector layer is each 1 μm or more and 100 μm or less, and The thickness of the positive electrode active material layer and the negative electrode active material layer is each 20 μm or more and 500 μm or less.

Citation Information

Patent Citations

  • Anode for lithium ion battery

    JP2009080971A